2020
DOI: 10.1101/2020.04.20.20064899
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemiological characteristics of COVID-19 in medical staff members of neurosurgery departments in Hubei province: A multicentre descriptive study

Abstract: Background The novel coronavirus (SARS-CoV-2) has infected a large number of healthcare workers in Hubei province, China. In addition to infectious and respiratory disease physicians, many doctors in other medical fields have been infected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 21 publications
0
29
1
Order By: Relevance
“…As COVID-19 has a significant different transmission profile from that of SARS and MERS [ 25 ], and surgical masks may perform differently from N95 masks, this type of pooled data and analysis may not help us to understand the utility of N95 masks in healthcare settings in the current COVID-19 pandemic. Including those cited in the above systematic review, we reviewed several observational studies that reported rates of infection in healthcare workers (either with or without wearing N95 masks) in close contact with COVID-19 patients in hospital settings [ [26] , [27] , [28] , [29] ]. Collectively, these studies reported COVID-19 infections in 132 of 4670 (2.83 %) healthcare workers who did not wear N95 masks, mostly during early stages of the pandemic and before the diagnosis was confirmed in the patients they were caring, and in 1 of 1636 (0.06 %) healthcare workers who did wear N95 masks as a part of the enhanced precaution.…”
Section: Resultsmentioning
confidence: 99%
“…As COVID-19 has a significant different transmission profile from that of SARS and MERS [ 25 ], and surgical masks may perform differently from N95 masks, this type of pooled data and analysis may not help us to understand the utility of N95 masks in healthcare settings in the current COVID-19 pandemic. Including those cited in the above systematic review, we reviewed several observational studies that reported rates of infection in healthcare workers (either with or without wearing N95 masks) in close contact with COVID-19 patients in hospital settings [ [26] , [27] , [28] , [29] ]. Collectively, these studies reported COVID-19 infections in 132 of 4670 (2.83 %) healthcare workers who did not wear N95 masks, mostly during early stages of the pandemic and before the diagnosis was confirmed in the patients they were caring, and in 1 of 1636 (0.06 %) healthcare workers who did wear N95 masks as a part of the enhanced precaution.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the prevalence of infection among the medical staff members in centers receiving COVID-19 patients has been reported as much higher than that of centers not receiving COVID-19 patients. 29 In the same way, physicians, nurses and health technicians with direct contact with COVID-19 patients have been more likely to be infected than those without, like clerical workers. 16 However, several studies have not identified a statistically significant difference in the proportion of infected HCWs from hospital units firstly involved in close contact with COVID-19 patients compared with intermediate- or low-risk units.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar manner, in the view of a large amount of SARS-CoV-2 hospitalized infected patients in the infectious and respiratory diseases units, working in the aforementioned facilities has been assumed to be risky too. Accordingly, the prevalence of infection among the medical staff members in centres receiving COVID-19 patients has been reported as much higher than that of centres not receiving COVID-19 patients [31]. In the same way, physicians, nurses, and health technicians with direct contact with COVID-19 patients have been more likely to be infected than those without, like clerical workers [18].…”
Section: Characteristics Of Hcws Who Were Infected By Sars-cov-19mentioning
confidence: 98%